The Effect of AtHKT1;1 or AtSOS1 Mutation on the Expressions of Na(+) or K(+) Transporter Genes and Ion Homeostasis in Arabidopsis thaliana under Salt Stress - Wang, Qian (Int J Mol Sci, 2019)
HKT1 and SOS1 are two key Na(+) transporters that modulate salt tolerance in plants. Although much is known about the respective functions of HKT1 and SOS1 under salt conditions, few studies have examined the effects of HKT1 and SOS1 mutations on the expression of other important Na(+) and K(+) transporter genes. This study investigated the physiological parameters and expression profiles of AtHKT1;1, AtSOS1, AtHAK5, AtAKT1, AtSKOR, AtNHX1, and AtAVP1 in wild-type (WT) and athkt1;1 and atsos1 mutants of Arabidopsis thaliana under 25 mM NaCl. We found that AtSOS1 mutation induced a significant decrease in transcripts of AtHKT1;1 (by 56–62% at 6–24 h), AtSKOR (by 36–78% at 6–24 h), and AtAKT1 (by 31–53% at 6–24 h) in the roots compared with WT. This led to an increase in Na(+) accumulation in the roots, a decrease in K(+) uptake and transportation, and finally resulted in suppression of plant growth. AtHKT1;1 loss induced a 39–76% (6–24 h) decrease and a 27–32% (6–24 h) increase in transcripts of AtSKOR and AtHAK5, respectively, in the roots compared with WT. At the same time, 25 mM NaCl decreased the net selective transport capacity for K(+) over Na(+) by 92% in the athkt1;1 roots compared with the WT roots. Consequently, Na(+) was loaded into the xylem and delivered to the shoots, whereas K(+) transport was restricted. The results indicate that AtHKT1;1 and AtSOS1 not only mediate Na(+) transport but also control ion uptake and the spatial distribution of Na(+) and K(+) by cooperatively regulating the expression levels of relevant Na(+) and K(+) transporter genes, ultimately regulating plant growth under salt stress.